ANALISIS FAKTOR KETAHANAN PANGAN DI NEGARA BERKEMBANG KAWASAN ASEAN - Abil Ihzan Mahendra; Girindra Mega Paksi (Journal of Development Economic and Social Studies, 2024)
In developing countries, particularly in the Southeast Asian region, food security serves as a form of national defense to safeguard the well-being of their populations. There are numerous factors that can affect the food security of a country. This research aims to elucidate the factors influencing food security in developing countries, specifically in Southeast Asia (Indonesia, Malaysia, Thailand, Vietnam, and the Philippines). The objective of this study is to define the factors related to phenomena associated with food security. The results of this research are expected to serve as a reference for various stakeholders and contribute to knowledge in the field of economics. The research methodology used is quantitative explanation, employing panel data analysis.The results of the study show that factors such as research and development in the agricultural sector, the availability of agricultural land, and policies related to the agricultural sector have a positive and significant impact. Conversely, the employmente in the agricultural sector has a negative and significant influence on food security. Meanwhile, the GDP of the industrial sector does not have a significant effect on food security.